2010
DOI: 10.1021/jm901805m
|View full text |Cite
|
Sign up to set email alerts
|

Phenylcinnamides as Novel Antimitotic Agents

Abstract: Compound 8H is a phenylcinnamide that induces G2/M-phase cell cycle arrest and cell death in cancer cell lines. Here we show that 8H exerts its cytotoxic activity through disruption of microtubule dynamics in vitro and in cell culture. A series of cinnamide derivatives were synthesized and evaluated, and several new compounds were identified that improve on the activity of the parent compound, with IC(50) values for induction of cell death ranging from 1 to 10 microM. Notably, these compounds retain potency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Based on their structural resemblance to phenylcinnamides, we considered tubulin as a potential target 31 for our active compounds. To investigate whether the antiproliferative activity of these compounds is due to an interaction with tubulin, we evaluated the effects of 3a–k on the polymerization of purified tubulin, using the highly potent CA-4 as reference (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their structural resemblance to phenylcinnamides, we considered tubulin as a potential target 31 for our active compounds. To investigate whether the antiproliferative activity of these compounds is due to an interaction with tubulin, we evaluated the effects of 3a–k on the polymerization of purified tubulin, using the highly potent CA-4 as reference (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…1) are shown to bind to tubulin, thereby causing an inhibition of its polymerization and alteration in the tubulin-microtubule equilibrium. 2831 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that compound 1a most likely derived its antiproliferative activity from an interaction at the colchicine site of tubulin, causing inhibition of tubulin polymerization [19]. To investigate whether the antiproliferative activities of the most active hybrid compounds ( 4e , 4i , 4m , 4o – p , 4r ) were related to an interaction with the microtubule system, these molecules were evaluated for their in vitro inhibition of the polymerization of purified tubulin [33].…”
Section: Biological Results and Discussionmentioning
confidence: 99%
“…Several laboratories reported that the phenylcinnamide scaffold showed anticancer activity against various human cancer cell lines. Phenylcinnamide derivatives with general structure 1 (Chart 1) are a class of compounds initially identified by Hergenrother et al as potential anticancer agents [18,19], with a moderate cytotoxic activity (IC 50 ranging from 1 to 10 μM). These compounds interact with micro-tubules by interfering with the dynamics of tubulin polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the reported biological properties of certain N-arylcinnamides and Nbenzylcinnamides that have showed in vitro antimycotic activity (Leslie et al, 2010) and the inhibition of the transcription of carcinogenic genes in infected cells (Sienkiewicz et al, 2007). The need of an easy, rapid and "green" protocol for the synthesis of these kind of compounds is necessary to explore new pharmacological targets, and in this order the challenge of the organic chemistry is currently focused on the design of novel methodologies that suppress the use of acyl chloride (including any dangerous reagent required for their synthesis) and promoting the direct condensation between carboxylic acids and amines, coupling that currently is performed using efficient promoters such as N,N'-dicyclohexylcarbodiimide (DCC) (Amma & Mallouk, 2004), (benzotriazol-1-yloxy)tripyrrolidinophosphonium hexafluorophosphate (ByPOB) (McCalmont, 2004;Baures et al;2002), triethylamine (Walpole, et al, 1993) and boron-based catalysts like BH 3 .…”
Section: Convenient and Scaleable Three-step Synthesis Of New N-benzymentioning
confidence: 99%